Representasi Maskulinitas Tokoh Lelaki Dalam Film Susah Sinyal - Jusuf Fadilah; Widarti Widarti; Dina Andriana (Jurnal Komunikasi, 2021)
Abstract  - This scientific research aims to determine the connotation and extension of Iwan, one of the supporting roles in the movie "Susah Sinyal", and the masculinity ideology of social development based on the analysis of Roland Barthes. The analytical methods used use qualitative research methods to give priority to descriptive interpretation and analysis of authors, and tend to give priority to analysis to generate more prominent thematic perspectives. This research has taken 10 photos in the movie "Susah Sinyal". These photos are inseparable from Iwan's role and are marked by explicit signs, to examine the implicit meaning of these images, from the connotation, extension, and mythological meaning spread in society Interpretation. The views and idols of people who were hyped up in their time.Keywords: Maskulinitas, konotasi, denotasi, mitos